INTERAKTIVITAS KOMENTAR VICTIM BLAMING DALAM KASUS NCII REBECCA KLOPPER DI MEDIA SOSIAL X - Armaulida, Annisa; Lukmantoro, Triyono; Hasfi, Nurul (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This study aims to determine the interactivity and the classification of victim blaming comments by X netizens towards NCII Rebecca Klopper case on @sosmedkeras post. This research uses a qualitative method with a netnography framework that focuses on X comments. Data collection techniques were carried out using archival data types and documented as screenshots or copy and paste of comments from @sosmedkeras post. This research used New media theory and interactivity theory to analyze the interactivity and classify victim-blaming comments against Rebecca Klopper. The results of this study show that the victim blaming comments on Rebecca Klopper occurs in two-way communication that dominantly carried out by anonymous accounts on X and elicited various pro and con responses. Pro responses are shown in the form of interactivity such as likes, reposts and comments demeaning the victim. Meanwhile, the con response is shown in the form of interactivity such as rebuttal comments and personal attacks agains the sender of the victim blaming comments. The study further identifies four categories of victim-blaming comments: 1) Blaming the act of recording sexual activities; 2) Sexual harassment; 3) Refusing to recognize Rebecca Klopper's status as a victim; and 4) Refusing to support or sympathize with the victim. Upon further examination, the deeply ingrained patriarchal culture in society and misunderstandings about NCII (Non-Consensual Dissemination of Intimate Images) case are the primary reasons for victim blaming phenomenon against Rebecca Klopper. To mitigate victim-blaming behavior in NCII cases, it is important to enhance education and raise public awareness about NCII, sexual behavior, and the concept of consent. This will contribute to creating a safer digital environment.